Development and evaluation of a seed drill for bed planting of wheat - fadlalmola, meera; El-Awad, Sheikh El Din; Mohamoud, Mohamoud (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
A field experiment was conducted at the Gezira Research Station, Wad Medani, Sudan for two seasons (2006/07 and 2007/08). It was laid out in a randomized complete block design with three replications. The objectives were to develop and evaluate a seed drill for bed planting of wheat that performs beds of 80 cm and sowing of wheat in three rows at spacing of 15 cm apart in a single pass. The machine was developed to replace the traditional seeding machine, enhance wheat seeding method in the short winter season, reduce the cost of crop establishment and improve crop growth. It was tested with the seed rates of 72, 107 and 143 kg/ha and compared with the traditional sowing methods (the conventional seed drill on flat and seed broadcasting + 80 cm ridges). No significant differences between treatments were evident in the soil bulk density and its corresponding soil moisture content for the two seasons. Results showed that the bed planting seed drill reduced the time for wheat seeding operation by about 42%. The developed bed planting seed drill with 72 and 107 kg/ha seed rates resulted in highly significant (P = 0.01) spike length in the first season only, whereas in the second season, it gave significantly (P = 0.05) lower crop emergence/m 2 and significantly (P = 0.05) higher plant height. No significant differences between treatments were detected in crop yield for the two seasons. Therefore, the lower seed rate of 72 kg/ha could be used with developed bed planting seed drill, which means the saving of about 50% of the recommended seed rate of 143 kg/ha. The developed seed drill for bed planting of wheat could be used successfully and with 50% of the recommended seed rate for wheat crop establishment in the Vertisol irrigated schemes of Sudan. أجريت هذه التجربة بمحطة بحوث الجزيرة بوادمدنى لموسمي 2006/2007 و2007/2008م. أستخدم فيها تصميم القطاعات العشوائية الكاملة بثلاث تكرارات. وكان الهدف تصميم وتقييم بذارة قمح للزراعة على مساطب  80 سم فى ثلاثة خطوط فوق سطح المسطبة على بعد 15سم في عملية آلية واحدة، بغرض تقليل الزمن المطلوب للزراعة،  الإسراع بعملية البذار في موسم الشتاء القصير، تقليل تكلفة تأسيس المحصول وتحسين أطوار نموه. تم اختبار البذارة بكميات بذور مختلفة (72، 107 و143 كجم/هكتار) مقارنة بالطرق التقليدية لزراعة القمح (البذار في سطور على سطح الأرض ونثر البذور + طراد 80سم). لم تكن هناك فروقات معنوية بين المعاملات على الكثافة الظاهرية للتربة ومحتوى الرطوبة. أظهرت النتائج أن البذارة المصممة قللت من الزمن المطلوب لعملية بذار القمح بحوالي 42%. كما أن استخدامها بمعدل 72 و 107 كجم/هكتار أعطى زيادة معنوية كبيرة (P = 0.01) في طول السنبلة للموسم الأول فقط، أما في الموسم الثاني فقد أعطت البذارة المصممة  وبمعدل الكميتين من التقاوي فروقات معنوية (P = 0.05)  في قلة عدد  البادرات للمتر المربع و زيادة فى طول النبات. لم تكن هناك فروق معنوية في اﻹنتاجية بين المعاملات للموسمين، ولذلك  فإن تقليل  معدل بذار القمح حتى 72 كيلوجرام للهكتار عند ٳستخدام البذارة المصممة يعمل  على توفير حوالي %50 من معدل التقاوى الموصى بها  وهو 143 كيلو جرام للهكتار. و عليه، يمكن استخدام البذارة المصممة بنجاح وبحوالي %50 من كمية التقاوى الموصى بها لتأسيس محصول  القمح بالمشاريع المروية في الأراضي الطينية بالسودان.